Survival rates of axial and tilted implants in the rehabilitation of edentulous jaws using the All-on-four™ concept: A systematic review - Sneha Harishchandra Gaonkar; Meena Ajay Aras; Vidya Chitre; Kennedy Mascarenhas; Bhavya Amin; Praveen Rajagopal (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this review was to evaluate the survival rate of axial and tilted implants in rehabilitation of edentulous jaws using all on four concept. Setting and Design: Systematic Review. Materials and Methods: A literature review was performed in MEDLINE, PubMed Central (PMC), Google scholar, Embase, Cochrane Central Register of Controlled Trials. Hand searches were conducted of the bibliographic of related journals and systematic reviews. A total of 380 articles were obtained from the intial screening process. Of these articles, 25 articles fulfilled the inclusion criteria. The authors performed evaluation of articles independently as well as data extraction and quality assessment. Statistical Analysis Used: Qualitative analysis. Results: The major prosthetic complication was the fracture of the acrylic prosthesis. The mean cumulative survival rate of implants (72-132 months) were 94% to 98%. The prosthesis survival rate (12 months) was between 99% to 100%. The averaged bone loss was 1.3 ±0.4 mm (12-60 months). No Significant difference was found between survival rates of axial and tilted implants nor between maxilla and mandible. Conclusion: All on four concept can be employed successfully in the edentulous patients with resorbed ridges while improving their quality of life and reducing morbidity. However,randomized clinical trials with large sampling size and long term follow up should be incorporated.